2008
DOI: 10.1128/aac.01393-07
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Screening for Genes Associated with Gliotoxin Resistance and Sensitivity in Saccharomyces cerevisiae

Abstract: Gliotoxin (GT) is a secondary fungal metabolite with pleiotropic immunosuppressive properties that have been implicated in Aspergillus virulence. However, the mechanisms of GT cytotoxicity and its molecular targets in eukaryotic cells have not been fully characterized. We screened a haploid library of Saccharomyces cerevisiae single-gene deletion mutants (4,787 strains in EUROSCARF) to identify nonessential genes associated with GT increased resistance (GT-IR) and increased sensitivity (GT-IS). The susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
10
0
2
Order By: Relevance
“…Moreover, the increased sensitivity to gliotoxin in S. cerevisiae Dyap1 implies that this gene is also essential to protect against gliotoxin-induced ROS. These data further the observations of Chamilos et al (2008) regarding the effects of gliotoxin on yeast mutants and future studies will explore the effects of gliotoxin on A. fumigatus Dyap1. Our observation that S. cerevisiae Dgsh1, severely deficient in GSH (Lee et al, 2001), exhibits greater resistance to gliotoxin than wild-type -and that complementation with GSH1 restores wild-type levels of gliotoxin sensitivity -further underpins our proposal that intracellular GSH levels play an important role in mediating gliotoxin cytotoxicity in fungi as has been noted in animals cells by Bernardo et al (2003).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, the increased sensitivity to gliotoxin in S. cerevisiae Dyap1 implies that this gene is also essential to protect against gliotoxin-induced ROS. These data further the observations of Chamilos et al (2008) regarding the effects of gliotoxin on yeast mutants and future studies will explore the effects of gliotoxin on A. fumigatus Dyap1. Our observation that S. cerevisiae Dgsh1, severely deficient in GSH (Lee et al, 2001), exhibits greater resistance to gliotoxin than wild-type -and that complementation with GSH1 restores wild-type levels of gliotoxin sensitivity -further underpins our proposal that intracellular GSH levels play an important role in mediating gliotoxin cytotoxicity in fungi as has been noted in animals cells by Bernardo et al (2003).…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, Cramer et al (2006) demonstrated that exogenous gliotoxin controlled the expression of the gli cluster in A. fumigatus and thereby regulated its own production. Chamilos et al (2008) studied the effect of gliotoxin on Saccharomyces cerevisiae, using a library of single-gene mutants (4787 strains), in an attempt to further elucidate mechanisms of gliotoxin cytotoxicity and identify novel drug targets in eukaryotic cells. Overall, 10 mutants exhibited increased resistance to gliotoxin while 3 were statistically more sensitive to exogenous gliotoxin, compared to wild-type.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to gain insight into the in vivo effects of gliotoxin exposure, Chamilos and colleagues [60] screened a yeast deletion library to identify strains that were sensitive or resistant to exogenous gliotoxin compared to wild type. While a number of gene deletions caused changes in the gliotoxin exposure profile, of particular note was the finding that deletion of cys3, which encodes a cystathionine g-lyase, caused sensitization to gliotoxin.…”
Section: Gliotoxin Functionality In Fungimentioning
confidence: 99%
“…that has been extensively studied because of its cytotoxic and immunosuppressive effects on mammalian cells [1,2]. Model eukaryotic fungal organisms (e.g., Saccharomyces cerevisiae) have been used to screen genes associated with GT resistance or sensitivity as a model system for the impact of GT on animal cells [3], however, little is known about the effect that this toxin has on other fungi. The production of GT within the Aspergillus genus is inconsistent, for example, pathogenic fungi like A. fumigatus can produce GT while A. niger and Aspergillus nidulans lack the gli cluster responsible for the biosynthesis of the toxin [4].…”
Section: Introductionmentioning
confidence: 99%